2006
DOI: 10.1128/jvi.00987-06
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus G9 Protein Is an Essential Component of the Poxvirus Entry-Fusion Complex

Abstract: The vaccinia virus G9R gene (VACWR087) encodes a protein of 340 amino acids with the following structural features that are conserved in all poxviruses: a site for N-terminal myristoylation, 14 cysteines, and a C-terminal transmembrane domain. Previous studies showed that G9 is one of eight proteins associated in a putative entry-fusion complex. Our attempt to isolate a mutant without the G9R gene was unsuccessful, suggesting that it is essential for virus replication. To further investigate its role, we const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…Nondisulfide-bonded forms of the L1 and F9 proteins were also made, but these exhibited no serological reactivity, indicating that correct folding was important for their immunogenicity (data not shown). Two additional MV surface proteins have since been identified, and these were not included in the synthesized microarrays (9,40,42,43,48,54). Use of protein microarrays to measure antibody levels has found useful applications in diverse fields during the past 5 years (12,49).…”
Section: Resultsmentioning
confidence: 99%
“…Nondisulfide-bonded forms of the L1 and F9 proteins were also made, but these exhibited no serological reactivity, indicating that correct folding was important for their immunogenicity (data not shown). Two additional MV surface proteins have since been identified, and these were not included in the synthesized microarrays (9,40,42,43,48,54). Use of protein microarrays to measure antibody levels has found useful applications in diverse fields during the past 5 years (12,49).…”
Section: Resultsmentioning
confidence: 99%
“…We found that F9-deficient MVs could bind to cells but that cytoplasmic cores were not detected by antibody labeling. A similar phenotype was found for other protein components of the putative entry/fusion complex (22,23,30,32,36,37). F9 shares many characteristics with components of the entry/fusion complex including (i) conservation among all sequenced poxviruses, (ii) postreplicative expression, (iii) association with the MV membrane, (iv) formation of intramolecular disulfide bonds by the poxvirus-encoded redox pathway, and (v) absence of an essential role in morphogenesis.…”
Section: Discussionmentioning
confidence: 72%
“…Initial experiments indicated that the protein was associated with MVs purified by sucrose density gradient centrifugation. Compared to L1, F9 was poorly soluble upon extraction with NP-40 or NP-40 plus DTT (data not shown) as found for some components of the entry/fusion complex (22,23). Evidence for the location of F9 in the MV membrane was obtained by surface biotinylation of purified MVs.…”
Section: Conservation Of the Vacv F9 Proteinmentioning
confidence: 92%
See 1 more Smart Citation
“…Historically, these studies have spanned both interactions of viruses with antibodies as well as studies by electron [27][28][29] and light microscopy [30] of various stages in the viral life cycle. Recent progress in both areas provides encouraging signs that the use of 3D electron microscopic approaches could also be invaluable in the physiological context.…”
Section: Virus-antibody Complexes and The Cellular Interfacementioning
confidence: 99%